Studi Kasus Perilaku Anak Hiperaktif Di SDN 3 Sukoharjo Kecamatan Bandung Kabupaten Tulungagung - Trisna, Evi Levia; Ana, Ria Fajrin Rizqy (Jurnal Simki Postgraduate, 2023)
Hyperactivity is a child who has attention deficit disorder who behaves like talking to himself, can't keep quiet, often leaves his seat or walks around in class, often acts strangely like throwing things, grabbing his friends' things, hard to talk to, not even connecting when talking. being asked, always looking for the teacher's attention, and children always ask too much of the teacher. The formulation of the research problem is how is the behavior of hyperactive children at SDN 3 Sukoharjo, Bandung District, Tulungagung Regency. This study aims to identify the behavior of hyperactive children at SDN 3 Sukoharjo, Bandung District, Tulungagung Regency. This research uses a qualitative descriptive approach using the case study method. The research instrument used observation sheets, interview sheets, and documentation. From the results of the case study it was proven that there were 2 children with hyperactivity disorder who were in class II and V of SDN 3 Sukoharjo. This the results of this study can be concluded that Subject A1 is a hyperactive student, not too aggressive and introverted. While student A2 is a student with excessive hyperactivity, often moves and is unable to concentrate. The results of this study can be used as input and material for consideration for future researchers.